Pedagogical Mediation for the Teaching of Philosophy in the School of General Studies of the University of Costa Rica, Rodrigo Facio Headquarters (I cycle, 2022) - Ortega Álvarez, Alejandro (2022)
This article is a proposal of Pedagogical Mediation for the teachers of the Section of Philosophy and Thought of the University of Costa Rica of the first academic cycle 2022. It is done from the theory of some intellectuals representative of Complexity and other current educational theories. Particularly, the contribution of Humberto Maturama, as a representative of Biopedagogy, in the use of "autopoiesis" as a fundamental concept to understand pedagogical practice as a source of freedom and creativity in learners of philosophical work from the functioning of living systems stands out. Based on these contributions and others, the author makes concrete proposals for the elaboration of pedagogical strategies in the Philosophy course of the aforementioned Section of the School of General Studies of the University of Costa Rica.